The delimitation of Giffenity for the Wold-Juréen (1953) utility function using relative prices: A note - Robert A. Sproule (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
In the study of Giffen behavior or "Giffenity", there remains a paradox. On the one hand, the Wold-Juréen (1953) utility function has been touted as the progenitor of a multi-decade search for those two-good, particular utility functions, which exhibit Giffenity. On the other hand, there is no evidence that the Wold-Juréen (1953) utility function has ever been fully evaluated for Giffenity, with perhaps one minor exception, Weber (The case of a Giffen good: Comment, 1997). But there, Weber showed that the Giffenity of Good 1 depends upon the relative magnitude of income vis-à-vis the price of Good 2. Weber's precondition is so vague that it lacks broad appeal. This paper offers a new and a clear cut precondition for Giffen behavior under the Wold-Juréen (1953) utility function. That is, we show that if the price of Good 1 is greater than or equal to the price of Good 2, then Good 1 is a Giffen good.
Keywords: A22; A23; D11; 330; Slutsky decomposition; Giffen paradox; Wold-Juréen (1953) utility function